Research of braking peculiarities of used cars - Mitunevičius, Valentinas; Nagurnas, Saulius (Transport, 2002)
This paper briefly describes some analysis of a car braking process – the peculiarities of car wheel-to-road adhesion, the influence of distiibution of braking forces on car stability between front and rear axles. The requirements of EU Directive 71/320/EEC to braking force coefficients of car front and rear axles are exposed. Structural designs of braking systems are analyzed with respect to their meeting the EU standards. Experimental measurements ofbraking force coefficients for some models of cars which are used in Lithuania, are presented with the analysis how these coefficients meet the EU standards. The analysis of test results, suggestions for the ratio of braking forces of car front and rear axles are presented.First Published Online: 19 Dec 2011